2022
DOI: 10.3389/fmed.2022.851310
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phage Cocktail BFC 1.10 in Combination With Ceftazidime-Avibactam in the Treatment of Multidrug-Resistant Pseudomonas aeruginosa Femur Osteomyelitis—A Case Report

Abstract: High-energy trauma with severe bone fractures can be complicated by infection, leading to the development of osteomyelitis. Pseudomonas aeruginosa is an important causative agent of such infections because of its high virulence profile and ability to develop resistance against a wide range of antimicrobials quickly. P. aeruginosa biofilms cause treatment failure and relapsing infections. Bacteriophages are viruses that can be used to treat biofilm-associated infections. Moreover, the combination of phages with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Phage therapy was also combined with antibiotics (phage-antibiotic synergy) to increase bacterial killing of MDR P. aeruginosa in vitro [ 138 , 139 ]. There are several case reports of a combination of antibiotics with phage therapy to treat resistant P. aeruginosa infections, particularly in cases of chronic infections: antibiotics in various reports consisted of ceftazidime in endovascular infection with bacteremia [ 140 ]; meropenem, tobramycin, and polymyxin B in endovascular infection with bacteremia [ 141 ]; cefiderocol in cranial osteomyelitis [ 142 ], meropenem and colistin in UTI [ 143 ], CAZ/AVI in femur osteomyelitis [ 144 ], piperacillin/tazobactam, tobramycin, and colistin in lung transplant recipients [ 145 ], and other conventional antibiotics for empyema [ 146 ]. However, to date there is no data on the efficacy of phage therapy in sepsis.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Phage therapy was also combined with antibiotics (phage-antibiotic synergy) to increase bacterial killing of MDR P. aeruginosa in vitro [ 138 , 139 ]. There are several case reports of a combination of antibiotics with phage therapy to treat resistant P. aeruginosa infections, particularly in cases of chronic infections: antibiotics in various reports consisted of ceftazidime in endovascular infection with bacteremia [ 140 ]; meropenem, tobramycin, and polymyxin B in endovascular infection with bacteremia [ 141 ]; cefiderocol in cranial osteomyelitis [ 142 ], meropenem and colistin in UTI [ 143 ], CAZ/AVI in femur osteomyelitis [ 144 ], piperacillin/tazobactam, tobramycin, and colistin in lung transplant recipients [ 145 ], and other conventional antibiotics for empyema [ 146 ]. However, to date there is no data on the efficacy of phage therapy in sepsis.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Clinical data on CAZ–AVI’s efficacy in treating BJIs are limited. Nonetheless, several reports mentioned that patients with osteomyelitis or arthritis caused by MDR/XDR-GNB were successfully treated with CAZ–AVI [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Thirteen case reports that described fourteen patients with BJI treated with CAZ–AVI which were published between 2017 and 2022 were selected for the analysis [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The characteristics of the retrieved patients are shown in Table 3 , together with those of the three patients we previously described.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Aside from antibiotics, new therapies such as bacteriophage cocktails, are also emerging. Recent studies, for example, have demonstrated the efficacy of bacteriophages against MRSA, especially in association with daptomycin and ceftaroline with a >3 log 10 CFU ml −1 reduction (Kebriaei et al 2022), and against P. aeruginosa in difficult-to-treat bone and soft tissue infections in combination with low ceftazidimeavibactam concentrations (two-fold lower than the standalone needed concentrations) (Racenis et al 2022).…”
Section: New Therapiesmentioning
confidence: 99%